Phase Angle Predicts Arterial Stiffness and Vascular Calcification in Peritoneal Dialysis Patients. Issue 4 (July 2017) - Sarmento-Dias, Margarida; Santos-Araújo, Carla; Poínhos, Rui; Oliveira, Bruno; Sousa, Maria; Simões-Silva, Liliana; Soares-Silva, Isabel; Correia, Flora; Pestana, Manuel
Objectives: Fluid overload (FO) is frequently present in peritoneal dialysis (PD) patients and is associated with markers of malnutrition, inflammation, and atherosclerosis/calcification (MIAC) syndrome. We examined the relationships in stable PD patients between phase angle (PhA) and the spectrum of uremic vasculopathy including vascular calcification and arterial stiffness and between PhA and changes in serum fetuin-A levels. Methods: Sixty-one stable adult PD patients were evaluated in a cross-sectional study (ST1). Phase angle was measured by multifrequency bioimpedance analysis (InbodyS10, Biospace, Korea) at 50 kHz. Augmentation index (AI), a surrogate marker of arterial stiffness, was assessed by digital pulse amplitude tonometry (Endo PAT, Itamar Medical, Caesarea, Israel). Vascular calcification was assessed by simplified calcification score (SCS). Serum fetuin-A levels were measured by ELISA (Thermo scientific; Waltham, MA, USA). Serum albumin was used as a nutritional marker, and serum C-reactive protein (CRP) was used as an inflammatory marker. The same assessments were carried out longitudinally (ST2) in the first 33 patients who completed 1 year of evaluation in ST1. Results: In ST1, patients with PhA < 6° had higher CRP levels, AI, and SCS and lower serum albumin and fetuin-A levels, in comparison with patients with PhA ≥ 6°. In addition, PhA was a predictor of both AI ((3 = -0.351, p = 0.023) and SCS > 3 (EXP (B) = 0.243, p = 0.005). In ST2, the increase of PhA over time was associated with decreases in both AI ( r = -0.378, p = 0.042) and CRP levels ( r = -0.426, p = 0.021), as well as with the increase in serum fetuin-A levels ( r = 0.411, p = 0.030). Conclusions: Phase angle predicts both arterial stiffness and vascular calcification in stable PD patients.